Brain Hemodynamics and Cerebrovascular Reactivity in Patients with Tension-Type Headache - Rizvan Ya. Abdullaiev; Valeriy I. Kalashnikov; Olena L Tovazhnyanska; Alexander N. Stoyanov; Oksana I. Kauk (Journal of Neurological Research And Therapy, 2019)
Introduction: Tension-type headache (TTH) is very common, with a lifetime prevalence in the general population ranging in different studies between 30% and 78%. TTH, divided into episodic and chronic types, introduced in the manual
Keywords: Transcranial dopplerography (TCD)